Barron's essential words for the TOEFL : - Matthiesen, Steven J. (Barron's Educational Series, Inc., 2014)
Approximately 500 words and their definitions are presented here for ESL students preparing to take the TOEFL. The book also presents detailed advice on ways that students can expand their English language vocabulary.--Publisher's description.